2008
DOI: 10.1002/zoo.20189
|View full text |Cite
|
Sign up to set email alerts
|

Role of sensory cues on food searching behavior of a captive Manta birostris (Chondrichtyes, Mobulidae)

Abstract: This study reports on the first experimental research designed specifically for Manta birostris behavior. The authors attempted to learn about the feeding behavior and environmental cues influencing this behavior, as well as general cognitive ability. The preconditioned Manta's ability to identify food, on the basis of a fraction of the ordinary food signal complex, was tested. The opening of cephalic fins was considered a good indicator of feeding motivation level. The study subject animal used its biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Ari and Correia (2008) reported an acute sense of smell from a captive oceanic manta ray. The observations in this study of adult males pursuing select females while ignoring other adult females in the area, suggest males are able to detect a female's reproductive state, adding further support that NF's are likely ovulating.…”
Section: Reproductive Cyclesmentioning
confidence: 98%
“…Ari and Correia (2008) reported an acute sense of smell from a captive oceanic manta ray. The observations in this study of adult males pursuing select females while ignoring other adult females in the area, suggest males are able to detect a female's reproductive state, adding further support that NF's are likely ovulating.…”
Section: Reproductive Cyclesmentioning
confidence: 98%
“…The devil rays, composed of 11 species in two genera ( Manta Walbaum and Mobula Rafinesque 1810), are the largest of all marine rays (Nelson, ; Compagno, ; Ari and Correia, ; Marshall et al, ). They are found circumglobally in tropical and subtropical marine environments including: the Yucatan Peninsula, New Zealand, parts of Australia, Baja California, Africa, Ecuador, Southern Japan, throughout Indonesia, at cleaning stations off of Hawaii, Bora Bora, and Yap, (Homma et al, ; Compagno and Last, ; Anderson, ; Duffy and Abbott, ; Dewar et al, ) and even occasionally in temperate areas as far north as Southern New England (Campbell and Munroe, ) and New Jersey (Fowler, ; Bigelow and Schroeder, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we suggest that M. birostris was preying on P. monodon. Even though the observed individual was seen with its cephalic fins closed at 16 m deep, suggesting a non-feeding behavior (Ari & Correia, 2008) and recent work has found that M. birostris mainly feeds on deep-water zooplankton (Burgess et al, 2016;, the possibility that this muninid crustacean could be a prey of Mobula spp. shall not be completely discarded as few studies have determined that zooplankton, shrimps, crabs and small fishes are key items on giant manta rays diet (Bigelow & Schroeder, 1953;Couturier et al, 2012;Rohner et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…The cephalic fins were closed while swimming across the water column 2 m above the seafloor, suggesting a non-feeding behavior (Ari & Correia, 2008). The widening of the branchial gills could not be assessed because of the presence of sucker-fishes below them, which impeded the determination of a definite feeding behavior.…”
Section: Resultsmentioning
confidence: 99%